Hiatal hernia: diagnostic and therapeutic approach - Dueñas, Felipe Huerta (International Surgery Journal, 2023)
Hiatal hernia is a common condition of the digestive system characterized by displacement of the stomach into the chest through the esophageal hiatus of the diaphragm. As research progresses and more scientific evidence accumulates, continued advances in the surgical approach to hiatal hernia are expected to occur. This will allow for a better understanding of the disease’s pathophysiology and the development of new surgical techniques and approaches that further improve the long-term outcomes and quality of life of patients with hiatal hernia.